Wideband printed MIMO/Diversity Monopole Antenna for WiFi/WiMAX applications - Chan, Hwang See; Abd-Alhameed,, Raed A.; Z. Abidin, Zuhairiah; J. McEwan, Neil; S. Excell, Peter (2012)
A novel printed diversity monopole antenna is presented for WiFi/WiMAX applications. The antenna comprises two crescent shaped radiators placed symmetrically with respect to a defected ground plane and a neutralization lines is connected between them to achieve good impedance matching and low mutual coupling. Theoretical and experimental characteristics are illustrated for this antenna, which achieves an impedance bandwidth of 54.5% (over 2.4–4.2 GHz), with a reflection coefficient 10 dB and mutual coupling 17 dB. An acceptable agreement is obtained for the computed and measured gain, radiation patterns, envelope correlation coefficient, and channel capacity loss. These characteristics demonstrate that the proposed antenna is an attractive candidate for multiple-input multiple-output portable or mobile devices.